UNMET PROSTHODONTIC NEEDS AND ORAL HEALTH RELATED QUALITY OF LIFE AMONG TRADERS IN AN URBAN KANO MARKET: A PILOT SURVEY - Oluwafeyisayo Francis Ikusika; albert Faiva Zirra; afamdi iwuchukwu; chukwuemeka Raymond Ngwu; Farida Bappah (Nigerian Dental Association, 2024)
ABSTRACT: Objectives: Prosthodontic needs may affect oral health quality of life among subsets of an urban population like traders in urban markets. This study therefore aimed to evaluate the impact of unmet prosthetic needs on Oral Health Related Quality of Life (OHRQoL) among traders in urban markets within Kano metropolis. Materials and Methods: Institutional Ethical approval was obtained. Study location was selected after a stratified sampling of available markets. A study proforma retrieving information on sociodemographic, prosthetic status and needs; and, the Oral Health Impact Profile-14 (OHIP-14) was administered on consenting participants. Retrieved data were summarized as frequencies, percentages and means. Prosthetic needs were quantified and assessed to derive patterns and odds ratios across participants sociodemographic characteristics. Rank Correlation and subgroup analyses were to assess the relationship between prosthetic need and OHIP-14 scores and how this is influenced by gender and age. Results: A total of 360 individuals participated in the study. There were 274 (76%) males and 86 (24%) females. Their ages ranged from 18 to 85 years with a mean age of 35.9 ± 14.8 years. A comparable percentage of participants were either married (48%), or had never been married (44.1%). Participants who identified as Muslim (84.7%) predominated, and Hausa/Fulani (69.4%) were the predominant ethnic identity. Many (48.1%) of participants had at least a secondary school level of education. About a fifth (79 or 21.9%) of the participants had a prosthodontic need. Unmet needs were present in 51(64.6%) of this segment of the participants. Females were more likely to have a prosthesis (OR = 2.01; 95% CI: 0.90, 4.74). Prostheses were more common among participants 50 years or older (OR=7.49; 95% CI:1.50, 37.29) and were about 3.5 times more likely to be found in individuals who had at least a secondary school education. Mean OHIP-14 scores was 1.3±3.9 in those without prosthetic needs and 13.1±12.7 for those with needs. Prosthetic need influenced OHIP=14 scores in all tested domains (p<0.001). Prosthetic needs correlated with OHIP-14 scores (rs=0.64, p<0.001). The correlation between prosthetic needs and OHIP-14 scores was stronger in females (p<0.001) and with increasing age (p<0.001). Conclusion: There was a high level of unmet prosthetic need within the studied population. Prosthetic need was inversely related to Oral Health Related Quality of Life. Increasing age and female gender were directly related to prosthetic needs and prosthetic status.